A Case of Reversible Paraparesis Following Celiac Plexus Block. Issue 1 (1st January 2001) - Kumar, Ashok; Tripathi, Shiva S.; Dhar, Debashish; Bhattacharya, Abhijit
Abstract : Background and Objectives: Permanent and acute reversible paraplegia following celiac plexus block (CPB) have been reported. We report a case of prolonged reversible paraparesis after alcohol celiac plexus block. Case Report: A 72-year-old man with primary multicentric pancreatic tumor and multiple hepatic metastases underwent alcohol celiac plexus neurolysis for severe abdominal pain radiating to the back. The patient had complete pain relief after the block but developed paresthesia of the left leg, which then spread to the right leg. Subsequently, loss of flexion and extension of the muscles supplying the left hip, knee, and foot developed. Deep tendon reflexes were brisk on the left compared to the right, and both plantar reflexes gave flexor responses. Magnetic resonance imaging and myelography were normal. Motor-evoked potential recordings showed a spinal cord lesion with involvement of the pyramidal and spinothalamic tracts. Somatosensory-evoked potentials indicated a relative sparing of dorsal column pathways. Physiotherapy was started, the sensory changes gradually subsided, and the patient was discharged 30 days after the block with clinically insignificant neurological deficit. Conclusions: Paraparesis following alcohol celiac plexus block may be reversible over an extended period of time.